Identification of SLC35A1 as an essential host factor for the transduction of multi-serotype recombinant adeno-associated virus (AAV) vectors - Xiujuan Zhang; Siyuan Hao; Zehua Feng; Kang Ning; Cagla Aksu Kuz; Shane McFarlin; Donovan Richart; Fang Cheng; Ander Zhang-Chen; Richenda McFarlane; Ziying Yan; Jianming Qiu (mBio)
ABSTRACT We conducted a genome-wide CRISPR/Cas9 screen in suspension 293 F cells transduced with rAAV5. The highly selected genes revealed after two rounds of screening included the previously reported KIAA0319L, TM9SF2, and RNF121, along with a cluster of genes involved in glycan biogenesis, Golgi apparatus localization, and endoplasmic reticulum penetration. In this report, we focused on solute carrier family 35 member A1 (SLC35A1), a Golgi apparatus-localized cytidine 5’-monophosphate-sialic acid (CMP-SIA) transporter. We confirmed that SLC35A1 knockout (KO) significantly decreased rAAV5 transduction to a level lower than that observed in KIAA0319L or TM9SF2 KO cells. Although SLC35A1 KO drastically reduced the expression of α2,6-linked SIA on the cell surface, the expression of α2,3-linked SIA, as well as the cell binding and internalization of rAAV5, was only moderately affected. Moreover, SLC35A1 KO significantly diminished the transduction of AAV multi-serotypes, including rAAV2 and rAAV3, which do not utilize SIAs for primary attachment. Notably, the SLC35A1 KO markedly increased transduction of rAAV9 and rAAV11, which primarily attach to cells via binding to galactose. Further analyses revealed that SLC35A1 KO significantly decreased vector nuclear import. More importantly, although the C-terminal cytoplasmic tail deletion (∆C Tail) mutant of SLC35A1 did not drastically decrease SIA expression, it significantly decreased rAAV transduction, as well as vector nuclear import, suggesting that the C-tail is critical in these processes. Furthermore, the T128A mutant significantly decreased SIA expression but still supported rAAV transduction and nuclear import. These findings highlight the involvement of the CMP-SIA transporter in the intracellular trafficking of rAAV vectors post-internalization.IMPORTANCErAAV is an essential tool for gene delivery in the treatment of genetic disorders; however, the mechanisms of rAAV transduction remain partially understood. GPR108 is vital for the transduction of most rAAV vectors, but not for rAAV5. We aimed to identify host factors that impact AAV5 transduction akin to GPR108. Using a genome-wide CRISPR/Cas9 screen in 293 F cells, we identified SLC35A1, a Golgi apparatus-localized CMP-sialic acid transporter that transports CMP-sialic acid from the cytoplasm into the Golgi apparatus for sialylation, is essential to rAAV transduction. Further studies across various AAV serotypes showed SLC35A1 significantly affects vector nuclear import post-internalization. These results underscore the crucial role of SLC35A1 in intracellular trafficking beyond the initial cell attachment of rAAV.